Asymmetric Effect of External Debt on Foreign Direct Investment (FDI): Empirical Study from Nigeria - Shuaibu, Mukhtar; Abdulhamid, Jabiru (MultiTech Publisher, 2023)
The paper examines the effect of external debt on FDI inflow in Nigeria between 1983 and 2021. Stationarity tests such Augmented Dickey Fuller (ADF), Phillips Perron (PP) as well as Guris (GUR) non-linearity unit root tests were employed to check the properties of the series. Non-linear Autoregressive Distributed Lag (NARDL) model was adapted to explore the relationship between the variables after confirming the mixed order of integration across the three testes. The Bound Test reveals the existence of a long-run relationship between the variables. According to the NARDL results; in the short-run a unit positive change in external debt would lead to decrease in FDI inflow by (1.165) while a unit negative change in external would lead to increase in FDI inflow by (1.360) and both are significance at 5% level of significance in short-run. The long-run results indicates that, the positive and negative change in external debt exhibit positive effect on net FDI inflow but only negative change is statistically significance at 5% level of significance. It is recommended that government should take steps in redemption of existing external debt and refrain from taking on any unnecessary new debt as these actions will not help the country's short run net FDI inflow and consequently, its overall economic growth.